2009
DOI: 10.1021/la803450y
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Interface Shape Evolution in Immiscible Polymer Blends via 3D Image Analysis

Abstract: The coordinate transformation (CT) method was applied to measure the local curvature of the interface of an immiscible polymer blend made of fluorescently labeled polystyrene (FLPS) and styrene-ran-acrylonitrile copolymer (SAN). The CT method involves the local parametrization of the interface by a quadratic polynomial to compute the local values of the mean (H) and the Gaussian (K) curvatures. Distributions of the curvatures at different annealing times were obtained by measuring H and K at many (typically 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 39 publications
4
83
0
Order By: Relevance
“…Notwithstanding the significant differences in how these co‐continuous systems are formed, there is substantial evidence that the underlying topology of systems produced by phase separation and by mechanical mixing is similar. Lopez‐Barron and Macosko found that the appearance and the hyperbolic interfacial curvature distributions of low interfacial tension, (less than roughly 2 mN/m) co‐continuous fluid systems prepared by mechanical mixing are similar to those measured in the late stages of spinodal decomposition . It is also worth noting that the curvature distribution of mechanically mixed systems shifts toward having a less hyperbolic and more parabolic character as interfacial tension increases …”
Section: Co‐continuous Fluid System Structures and Quiescent Coarsenimentioning
confidence: 58%
See 2 more Smart Citations
“…Notwithstanding the significant differences in how these co‐continuous systems are formed, there is substantial evidence that the underlying topology of systems produced by phase separation and by mechanical mixing is similar. Lopez‐Barron and Macosko found that the appearance and the hyperbolic interfacial curvature distributions of low interfacial tension, (less than roughly 2 mN/m) co‐continuous fluid systems prepared by mechanical mixing are similar to those measured in the late stages of spinodal decomposition . It is also worth noting that the curvature distribution of mechanically mixed systems shifts toward having a less hyperbolic and more parabolic character as interfacial tension increases …”
Section: Co‐continuous Fluid System Structures and Quiescent Coarsenimentioning
confidence: 58%
“…Furthermore, experimentally measured and dynamically scaled mean and Gaussian curvature distributions for these systems are super‐imposable on single master curves consistent with self‐similar coarsening throughout this linear coarsening regime . In addition, Lopez‐Barron computed the genus/volume as a function of time for one system at two phase volume fractions and found it fell continuously with time. The genus is an important topological feature which represents the number of holes in a surface.…”
Section: Co‐continuous Fluid System Structures and Quiescent Coarsenimentioning
confidence: 76%
See 1 more Smart Citation
“…This is usually attributed to the formation of a hydrodynamically percolated particle network of the lled particles. [43][44][45] However, upon annealing, the coarsening process differs very much for pure blend and the particle lled blends. For 50/50 PP/PS blend with co-continuous morphology, all the interface of the two phases are practically connected and form a channel throughout the blend.…”
Section: Rheological Behavior Of Pp/ps Blends With Particles At the Imentioning
confidence: 99%
“…Thus, the blends also can be divided into another three kinds: miscible, immiscible, and partially miscible blends. The miscibility of blends has been widely studied . Wu points out that the integrated crystallization behavior occurs in the immiscible systems because of the macrophase separation of blends.…”
Section: Introductionmentioning
confidence: 99%